Theoretical foundations of movement control in the process of training athletes in combat sports - Novakovsky S.V.; Maksimovich V.A.; Rudenik V.V. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to develop theoretical and methodological foundations for the formation and improvement of movement control mechanisms in the process of training athletes in combat sports. Results and conclusions. It has been established that movement control mechanisms ensure the implementation of elements of dynamic posture, main and corrective control movements. To increase the effectiveness of competitive exercise techniques, it is necessary to form and improve movement control mechanisms in a certain sequence, determined by the interrelation of elements in the movement system. Based on the relationship in the motor action of the elements of posture and control movements (main and corrective), the theoretical and methodological foundations for the formation and improvement of movement control mechanisms in the process of technical and tactical training of athletes in combat sports have been developed. An algorithm has been determined for the development of methods for the formation and improvement of movement control mechanisms in the process of training wrestlers, taking into account the technique being mastered and in relation to a specific movement situation.